Report on Capacity Building in the Scaling of Off-Season Crop Diversification and Integrated Pests and Disease Management in Mali: Training Workshop Report - Suh, Neville; Doumbia, Salif; Kone, Yaya; Dossou-Yovo, Elliott (2024)
Effective acceleration of climate-smart agricultural (CSA) technologies into agricultural policy and programs requires sustained capacity development of local practitioners and actors participating in agriculture. The AICCRA Mali cluster, led by AfricaRice, organized a capacity-building workshop to strengthen the technical and human capacity of lead farmers, extension agents, and other actors engaged in the rice value chain to accelerate the adoption of CSA practices and technologies in Mali. The capacity-building sessions focused on CSA concepts and approaches for scaling in rice-based systems. A two-day training session on off-season crop diversification and integrated pests and disease management (IPDM) was organized by the AICCRA project. Twenty-six participants attended the training sessions, including extension agents and lead farmers from 14 organizations and structures in Sikasso, Segou, and Koulikoro regions. The training also included 4 female participants. Participants were equipped with new skills and capacities to effectively deploy and disseminate the aforementioned CSA technologies in rice-based systems. Furthermore, to contribute to the acceleration of CSA technology in Mali, participants, particularly lead farmers and extension agents, have decided to educate and encourage other farmers on the benefits of adopting CSA technologies in their respective communes and villages. The report shows the close linkages between climate change adaptation, livelihood, sustainable development, and capacity building and reflects increasing interest from diverse actors engaged in climate actions in Mali.